The prevalence of bovine mastitis-associated Staphylococcus aureus in China and its antimicrobial resistance rate: A meta-analysis - Wang, Kuan; Cha, Jinlong; Liu, Kai; Deng, Jianming; Yang, Bowen; Xu, Hui; Wang, Juyu; Zhang, Limei; Gu, Xiaolong; Huang, Cuiqin; Qu, Weijie (Frontiers in Veterinary Science, 2022)
To optimize the Staphylococcus aureus control program, a meta-analysis was conducted to investigate the epidemiology and antimicrobial resistance (AMR) profile of bovine mastitis associated S. aureus in China from 2000 to 2020. A total of 33 publications from PubMed, Google scholar and China National Knowledge Infrastructure (CNKI) database were included in our research, of the 9 publications that involved antimicrobial resistance (AMR) test. The pooled prevalence of S. aureus was 36.23% and subgroup analysis revealed that prevalence dropped from 2000−2010 to 2011−2020, looks China on the right track. The pooled AMR rate indicate the isolates were most resistant to β-Lactams (50.68%), followed by quinolones (36.23%), macrolides (34.08%), sulfonamides (32.25%), tetracyclines (27.83%), aminoglycosides (26.44%), lincosamides (23.39%) and amphenicol (10.33%). Both the pooled prevalence and AMR of S. aureus in China are higher than western countries such as Germany, Belgium, Ireland and the United Sates, that these countries have long animal husbandry history and good management. Thus, there is still room to improve the treatment of S. aureus associated bovine mastitis in China.